Let's analyze the equation step by step to determine whether it is true or false:
The original equation is: \[ (4\sqrt{8}) - 24 \cdot (\sqrt{8})^{16} \]
First, simplify \(4\sqrt{8}\): \[ \sqrt{8} = 8^{1/2} = (2^3)^{1/2} = 2^{3/2} \] Thus, \[ 4\sqrt{8} = 4 \cdot 2^{3/2} = 2^2 \cdot 2^{3/2} = 2^{2 + 3/2} = 2^{(4/2) + (3/2)} = 2^{7/2} \]
Now simplify \((\sqrt{8})^{16}\): \[ (\sqrt{8})^{16} = (8^{1/2})^{16} = 8^{(1/2) \cdot 16} = 8^8 \] And since \(8 = 2^3\), we have: \[ 8^8 = (2^3)^8 = 2^{24} \]
Now, multiplying: \[ -24 \cdot (2^{24}) = -24 \cdot 2^{24} = -2^3 \cdot 2^{24} = -2^{27} \]
Now, combining the two yields: \[ 2^{7/2} - 2^{27} \]
Now let's examine \(8^{-48}\): \[ 8^{-48} = (2^3)^{-48} = 2^{-144} \]
Now we compare \(2^{7/2} - 2^{27}\) and \(2^{-144}\). Clearly, \(2^{7/2}\) and \(2^{27}\) are positive numbers, while \(2^{-144}\) is also a positive number, but they cannot be equal or equal to 0.
Therefore, the equation is false. The correct choice is:
False, because the exponents should be added rather than multiplied.